Genetic determinants of texture in strawberry fruits - Buchanan, Aram James (2001)
Fruit texture is a quantitative trait believed to be determined by a number of genetic loci. In order to identify genes in strawberries that are specifically associated with texture a cross was made between a cultivar with firm fruits and a cultivar with soft fruits. The resultant population of 269F( plants produced ripe fruits whose firmness values differed over a five-fold range. Pools of twenty plants having either the softest or firmest fruits were analysed by two methods. The first, suppressive subtractive hybridisation initially indicated that many genes were differentially expressed in fruits from both the firm and soft pools. Differential hybridisation of 80 subtracted cDNA clones from each pool with the cDNA subtracted from each pool showed that many of the cDNAs were common to firm and soft fruit. When the subtracted cDNAs were hybridised with unsubtracted eDNA several clones from each pool appeared to be enhanced. However, northern analysis was unable to confirm these data. The second method used cDNA-AFLP to detect differentially expressed genes in the pools of firm and soft fruit. Using one set of amplification primers, bands corresponding to 27 cDNA fragments specific to either firm or soft fruit pools were resolved on a polyacrylamide gel. These fragments were cloned and sequenced but they had no obvious homology with genes associated with cell wall metabolism. Northern anlaysis indicated that the cloned cDNA-AFLP fragments represented polymorphisms unrelated to texture. One cDNA clone, AFLP-S 13, appeared to have higher levels of the corresponding transcript in fruits from the soft parent and soft pool. Although this clone was upregulated during ripening its expression was neither fruit specific nor correlated with texture. The expression of genes associated with cell wall metabolism including cell. cel2 and expansin was also investigated in the segregating population.